Did decentralisation affect citizens' perception of the European Union? The impact during the height of decentralisation in Europe - Vassilis Tselios; Andrés Rodríguez-Pose (Economies, 2020)
The aim of this paper is to assess the extent to which different levels of decentralisation across regions of the European Union (EU) affected citizens' perceptions about European integration over the period 1973-2002. The paper uses Eurobarometer Surveys to explore by means of multinomial logistic regressions whether decentralisation was an important factor behind the varying perceptions about Europe. Two dimensions of decentralization-political and fiscal-are considered in the analysis, alongside several compositional and contextual effects. The results of the analysis show that fiscal decentralisation was fundamental for citizens' support for European integration, while there is limited evidence that political decentralisation played a similar role. Hence, while fiscal decentralisation may have given prominence to the economic benefits of European integration, political decentralisation was more associated with its economic costs. Taking into account that history matters, this paper raises potentially interesting insights for the design of policies aimed at promoting social cohesion.
Keywords: H30; H72; 330; European Union; fiscal decentralisation; perceptions of attitudes; political decentralisation; regions